2004
DOI: 10.1002/cncr.20472
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and survival prediction in terminal cancer patients

Abstract: BACKGROUND.It remains unclear whether health-related quality of life (HRQoL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 53 publications
4
68
2
2
Order By: Relevance
“…The median survival time was 26 days [95% confidence interval (CI), [22][23][24][25][26][27][28][29]. The number of men was 100 (47.8%).…”
Section: Resultsmentioning
confidence: 99%
“…The median survival time was 26 days [95% confidence interval (CI), [22][23][24][25][26][27][28][29]. The number of men was 100 (47.8%).…”
Section: Resultsmentioning
confidence: 99%
“…Identification of such factors could improve prognostic accuracy and facilitate health care providers' decision making in selecting the most appropriate care plan [14]. Prior studies have shown the following to have predictive value for assessing the length of survival of terminal cancer patients: performance status [8-10, 14, 40], pain [40], fatigue [8,10,39], clinical symptoms [8,40], and quality of life [12,36,64]. Some studies of cancer patients, including patients not necessarily in a terminal phase, have identified quality of life as having an important prognostic factor [6,16,20].…”
Section: Introductionmentioning
confidence: 99%
“…A breast cancer survivor's physical well-being has most consistently been found to be predictive of survival, [5][6][7][8][9] but several studies have found that even this QOL measure, particularly when taken soon after diagnosis or for women with early-stage breast cancer, is often not associated with prognosis. 6,10,11 Aspects of a breast cancer survivor's social and/or psychosocial well-being have also been examined, [12][13][14] with several of the studies suggesting that greater social support may be associated with longer survival.…”
Section: Introductionmentioning
confidence: 99%